Communication of Dependent Messages Over Compound Channels - Cheng, Zhong (Université d'Ottawa / University of Ottawa, 2015)
In the communication of multimedia content, certain dependency structure often exists among the source-coded messages by different source coding techniques, where by "dependency" we mean the dependent contributions of the messages to the overall reconstruction quality. Motivated by such notion of dependency, this thesis considers the problem of communicating dependent source-coded messages over compound channels, which include the attractive wireless channels and packet-loss channels. In this thesis we propose a novel framework to model arbitrary dependency structure among source-coded messages from the source-reconstruction perspectives, and formulate the problem of communicating such messages over compound channels as the problem of maximizing the average utility at the receiver. Over discrete memoryless channels (DMC), we derive the expression of maximal achievable utility, which appears to be governed by the channel coding theorem. Over degraded compound channels, we study analytically the maximal achievable utility by superposition codes. To achieve the maximal utility, the encoder chooses the best sub-chain in the utility graph and encodes it using the best superposition code. For the case of two source-coded messages, we show that the maximal utility achieved by superposition codes is the maximum among all coding schemes. Since in practice layered codes (LC) and multiple description codes (MDC) are two most attracted source coding schemes which induce different dependency structures among coded messages, we numerically evaluate the maximal achievable utility for sources coded with those two source coding schemes communicated over DMC and degraded compound channels respectively, and show the impact of communication delay and channel condition on their respective achievable utilities. In addition, for communicating a Gaussian N(0,1) independent identically distributed (i.i.d.) sequence over degraded compound channels, the joint source channel coding schemes are considered and the minimal achievable distortion is derived and compared for different combinations of source and channel codes. It is shown that the combination of LC and superposition codes outperforms other coding schemes. The comparative behaviour among those techniques is further demonstrated by the experimental results. Practically, we study the performances of various coding schemes for communicating two dependent messages over quasi-static Rayleigh fading channels, which include conventional channel codes, time sharing codes, and a low-density parity-check (LDPC) based coding scheme, termed Bi-LDPC codes. The success rates and the throughput of the considered coding schemes are compared. For communicating a Gaussian N(0,1) source sequence encoded by LC and MDC respectively over quasi-static Rayleigh fading channels, the average distortion is also compared among different channel coding schemes. It appears that Bi-LDPC codes, conventional channel codes encoding both messages, and time sharing type-2 (TS-2) codes, each has their advantage over different region of signal-to-noise ratio (SNR), compared with each other.
Keywords: Channel coding